Resonance Raman spectroscopic study for radial vibrational modes in ultra‐thin walled TiO2 nanotubes. (21st January 2015) - Antony, Rajini P.; Dasgupta, Arup; Mahana, Sudipta; Topwal, D.; Mathews, Tom; Dhara, Sandip
<x xml:space="preserve">Abstract</x> The study reports the observation of radial vibrational modes in ultra‐thin walled anatase TiO2 nanotube powders grown by rapid breakdown anodization technique using resonant Raman spectroscopic study. The as‐grown tubes in the anatase phase are around 2–5 nm in wall thickness, 15–18 nm in diameter and few microns in length. The Eg(ν1, ν5, ν6) phonon modes with molecular vibrations in the radial direction are predominant in the resonance Raman spectroscopy using 325 nm He–Cd excitation. Multi‐phonons including overtones and combinational modes of Eg(ν1, ν5, ν6) are abundantly observed. Fröhlich interaction owing to electron–phonon coupling in the resonance Raman spectroscopy of ultra‐thin wall nanotubes is responsible for the observation of radial vibrational modes. Finite size with large surface energy in these nanotubes energetically favor only one mode, B1g(ν4) with unidirectional molecular vibrations in the parallel configuration out of the three Raman modes with molecular vibration normal to the radial modes. Enhanced specific heat with increasing temperatures in these nanotubes as compared to that reported for nanoparticles of similar diameter may possibly be related to the presence of the prominent radial mode along with other energetic phonon mode. The findings elucidate the understanding of total energy landscape for TiO2 nanotubes. Copyright © 2015 John Wiley & Sons, Ltd.